2020
DOI: 10.1016/j.adolescence.2020.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Bored and online: Reasons for using social media, problematic social networking site use, and behavioral outcomes across the transition from adolescence to emerging adulthood

Abstract: Introduction:The current study examined motivations for social networking site use across three years during the transition from late adolescence to emerging adulthood. While research has been conducted examining reasons for social networking site usage and behavior, the clear majority have focused on samples of undergraduate college students and are cross-sectional.Methods: Changes in motivations for using social networking sites were examined in relation to problematic social networking site use and several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
102
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(136 citation statements)
references
References 57 publications
9
102
0
8
Order By: Relevance
“…Regarding the media activity searching for information, our analyses suggest that this activity can weaken the associations between other media activities and behavioral di culties, especially externalizing behavioral problems and less prosocial behavior. This is in line with ndings of another recent study showing that social media use for the purpose of searching for information is not associated with any negative outcomes [37]. One possible explanation is that using media for academic purposes such as doing homework is bene cial for their behavioral adjustment.…”
Section: Associations Between Media Usage and Behavioral Strengths Ansupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding the media activity searching for information, our analyses suggest that this activity can weaken the associations between other media activities and behavioral di culties, especially externalizing behavioral problems and less prosocial behavior. This is in line with ndings of another recent study showing that social media use for the purpose of searching for information is not associated with any negative outcomes [37]. One possible explanation is that using media for academic purposes such as doing homework is bene cial for their behavioral adjustment.…”
Section: Associations Between Media Usage and Behavioral Strengths Ansupporting
confidence: 90%
“…Furthermore, studies exploring different -academic as well as entertaining -media activities in the same study are rare [36,37]. A very recent study showed that the use of social media for the purpose of searching for information was not associated with negative mental health outcomes, whereas social media use for other purposes was [37]. This nding suggests that searching for information is a media activity whose effects on behavioral adjustment differ from effects of other media activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nachgewiesen ist mittlerweile, dass Langeweile zu vermehrtem, suchtartigen Smartphone-Gebrauch [81,50], zu Internetsucht [16,65,91,101], Spielsucht und Computerspielsucht [33,45] führen kann. Zudem erhöht sie das Risiko für den pathologischen Gebrauch von sozialen Online-Netzwerken [13,86] und von Pornografie [11,25]. Einige Autoren heben hervor, dass gerade die Nutzung aus Langeweile mit langfristig nachteiligen Folgen verbunden ist.…”
Section: Langeweile In Psychiatrie Und Neurologieunclassified
“…Einige Autoren heben hervor, dass gerade die Nutzung aus Langeweile mit langfristig nachteiligen Folgen verbunden ist. So bemerken beispielsweise Stockdale und Coyne [86] in ihrer Diskussion: "Die aktuelle Studie unterstützt die wachsende Anzahl an Studien, die darauf hinweisen, dass die Nutzung von sozialen Online-Netzwerken zur Bekämpfung von Langeweile … mit einem erhöhten Risiko verbunden sein kann, pathologische Tendenzen und Verhaltensmuster gegenüber sozialen Online-Netzwerken zu entwickeln. 4…”
Section: Langeweile In Psychiatrie Und Neurologieunclassified